Two pathways to self‐forgiveness: A hedonic path via self‐compassion and a eudaimonic path via the reaffirmation of violated values. (20th March 2017) - Woodyatt, Lydia; Wenzel, Michael; Ferber, Matthew
Abstract : Self‐forgiveness is often measured as a hedonic end‐state, as the presence of positive affect and the absence of negative affect towards the self following a wrongdoing. However, self‐forgiveness is also referred to as a difficult process. Self‐forgiveness as a process of accepting responsibility and working through one's wrongdoing is a substantially un ‐hedonic – it is likely to be uncomfortable and at times painful. In this study, we examine two pathways to self‐forgiveness: a hedonic focused pathway (via self‐compassion) and a eudaimonic pathway (via reaffirmation of transgressed values). Across two studies, the data suggest that following interpersonal transgressions, self‐compassion reduces self‐punitiveness and increases end‐state self‐forgiveness (Study 1) via a reduction in perceived stigma (Study 2). In contrast, value reaffirmation increases the process of genuine self‐forgiveness and reduces defensiveness (Study 1) via increased concern for shared group values (Study 2), in turn increasing desire to reconcile (Study 1), and amend‐making and end‐state self‐forgiveness 1 week following the intervention (Study 2). The results suggest that both pathways can lead to self‐forgiveness; however, following a transgression, self‐forgiveness via a eudaimonic pathway offers greater promise for meeting the needs of both offenders and victims.